Endoplasmic reticulum stress response pathway-mediated cell death in ovarian cancer - Chen, Qiaochu; Li, Chan; Wei, Wei; Li, Jia; Liu, Fangyuan; Fu, Yuqian; Tang, Liping; Han, Fengjuan (Frontiers in Oncology, 2024)
The endoplasmic reticulum (ER) is one of the largest organelles, and Endoplasmic Reticulum Stress Response Pathway is a series of responses triggered by the homeostatic imbalance of the ER and the state in which unfolded or misfolded proteins accumulate in the ER, which can trigger cell death. Cell death plays a crucial role in the development of diseases such as gynecological oncology. Herein, we review the current research on the response and ovarian cancer, discussing the key sensors (IRE1, PERK, ATF6), and the conditions under which it occurs (Ca 2+ homeostasis disruption, hypoxia, others). Using the response as a starting point, provide a comprehensive overview of the relationship with the four types of cell death (apoptosis, autophagy, immunogenic cell death, paraptosis) in an attempt to provide new targeted therapeutic strategies for the organelle-Endoplasmic Reticulum Stress Response Pathway-cell death in ovarian cancer therapy.